2003
DOI: 10.1016/s0895-7061(03)00859-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of left ventricular hypertrophy in patients with mild hypertension in primary care: impact of echocardiography on cardiovascular risk stratification

Abstract: A substantial proportion of mildly hypertensive patients presenting in primary care have LVH determined by ECHO. Our results suggest that this procedure could significantly improve cardiovascular risk stratification in those patients with multiple risk factors, but no evidence of target organ damage by routine investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 34 publications
2
29
1
5
Order By: Relevance
“…1 K The usual evaluation of these patients in primary health care does not include the assessment of target organ damage. 15 What this study adds K The routine evaluation of CVR carried out in Primary Health Care (PHC) may lead to underestimating the risk of hypertensive patients, classifying many of them with a CVR lower than that corresponding to them. K In the present study, with the usual approach performed in PHC, drug treatment should have been initiated in 22 patients (14.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 K The usual evaluation of these patients in primary health care does not include the assessment of target organ damage. 15 What this study adds K The routine evaluation of CVR carried out in Primary Health Care (PHC) may lead to underestimating the risk of hypertensive patients, classifying many of them with a CVR lower than that corresponding to them. K In the present study, with the usual approach performed in PHC, drug treatment should have been initiated in 22 patients (14.1%).…”
Section: Discussionmentioning
confidence: 99%
“…K Those patients who, after this first assessment, have a low and above all moderate CVR should be measured for MA as a first evaluation of the presence of target organ damage, since this is an easy to perform and cost-effective test within the reach of all PHC professionals. 15 who found that the performance of an ECHO may be especially useful in patients who, after an initial assessment that included MA, were classified as having moderate CVR. In this group, 40% were reclassified to high risk according to the ECHO results.…”
Section: Discussionmentioning
confidence: 99%
“…2,14 Moreover, left ventricular mass is considered a risk factor of stroke. 5,[15][16][17] However, the effect of the interaction between physical activity and LVH on the risk of stroke has rarely been investigated. In a recent case-control study, Rodriguez et al 5 observed a significant association between increased left ventricular mass and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The enlargement of individual myocytes in LV has been considered an adaptation to increased blood pressure. However, non-hemodynamic factors may also be involved in the pathogenesis of LVH since it can be found in patients with only mild hypertension (Martinez et al, 2003). Cardiac hypertrophy has been studied using 3 representative models: aortic coarctation, monolayer cells cultured on stretchable mesh, and cardiac myocyte culture stimulated with different trophic factors.…”
Section: Discussionmentioning
confidence: 99%